2019
DOI: 10.3389/fphar.2019.00111
|View full text |Cite
|
Sign up to set email alerts
|

The New Paradigms in Clinical Research: From Early Access Programs to the Novel Therapeutic Approaches for Unmet Medical Needs

Abstract: Despite several innovative medicines gaining worldwide approval in recent years, there are still therapeutic areas for which unsatisfied therapeutic needs persist. For example, high unmet clinical need was observed in patients diagnosed with type 2 diabetes mellitus and hemophilia, as well as in specific age groups, such as the pediatric population. Given the urgent need to improve the therapy of clinical conditions for which unmet clinical need is established, clinical testing, and approval of new medicines a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…Furthermore, we found that the rate of new drug approvals for breast cancer has dramatically increased over the last 30 years, compared to earlier decades, in part driven by the development of targeted therapeutics [3]. This trend matches the acceleration of new drug approvals seen across the field of oncology as a whole [4,5], which results from the impressive progress in translational cancer research and from the evolving regulatory environment [6,7]. Together, these factors have profoundly changed the way in which new cancer drugs are discovered, studied, reviewed, and approved [8][9][10].…”
Section: Introductionmentioning
confidence: 57%
“…Furthermore, we found that the rate of new drug approvals for breast cancer has dramatically increased over the last 30 years, compared to earlier decades, in part driven by the development of targeted therapeutics [3]. This trend matches the acceleration of new drug approvals seen across the field of oncology as a whole [4,5], which results from the impressive progress in translational cancer research and from the evolving regulatory environment [6,7]. Together, these factors have profoundly changed the way in which new cancer drugs are discovered, studied, reviewed, and approved [8][9][10].…”
Section: Introductionmentioning
confidence: 57%
“…Given the clinical relevance of irADRs and considering that innovative drugs are increasingly authorized by accelerated procedures (Scavone et al, 2017b;Scavone et al, 2017a), further safety investigations in real-life context are necessary (Scavone et al, 2019). We believe that our results could be shared with clinicians that dailies prescribe and administer ICIs or monoclonal antibodies in general.…”
Section: Discussionmentioning
confidence: 76%
“…Disease state is one of the most important factors to consider when determining if a drug should be prioritized for precision dosing. The integration of precision dosing is likely to be most helpful in areas of high unmet medical need (Darwich et al, 2017), which include infectious disease, hematology, immunology/transplantation, oncology, neurology, and other therapeutic areas noted by Scavone and colleagues (Scavone et al, 2019). Disease related morbidity, mortality, and progression can be quite variable and can greatly impact the need for drug dosing individualization.…”
Section: Disease State Considerationsmentioning
confidence: 99%